Physiological and skill demands of `on-side` and `off-side` games - Gabbett, T. J.; Jenkins, D. G.; Abernethy, B. (The Journal of Strength and Conditioning Research, 2010)
This study investigated the physiological and skill demands of `on-side` and `off-side` games in elite rugby league players. Sixteen male rugby league players participated in `on-side` and `off-side` games. Both small-sided games were played in a 40-× 40-m playing area. The `off-side` game permitted players to have 3 `plays` while in possession of the ball. Players were permitted to pass backward or forward (to an `off-side` player). The `on-side` game also permitted players to have 3 `plays` while in possession of the ball. However, players were only permitted to pass backward to players in an `on-side` position. Heart rate and movement patterns (via global positioning system) were recorded continuously throughout both games. Data were collected on the distance covered, number of high-acceleration and velocity efforts, and recovery between efforts. Video footage was also taken to track the performance of the players. Post hoc inspection of the footage was undertaken to count the number of possessions and the number and quality of disposals. In comparison to `on-side` games, `off-side` games had a greater number of involvements ("touches"), passes, and effective passes. However, the cognitive demands of `on-side` games were greater than `off-side` games. `Off-side` games resulted in a greater total distance covered, greater distance covered in mild and moderate accelerations, and greater distance covered in low, moderate, and high-velocity efforts. There were also a greater number of short duration recovery periods between efforts in `off-side` games. The results of this study demonstrate that `off-side` games provide greater physiological and skill demands than `on-side` games. `Off-side` games may provide a practical alternative to `on-side` games for the development of skill and fitness in elite rugby league players.